Donor and newborn profiles and their influence on donation volume and duration: a cross-sectional study in a Spanish human milk bank - Katherine Flores-Rojas; Mercedes Gil-Campos; Isabel Lacort-Peralta; María José Párraga-Quiles; Belén Pastor-Villaescusa (BMC, 2024)
Abstract Background Human milk banks are essential facilities to provide donated human milk (DHM) to preterm and term infants with health complications. Little is known regarding milk bank donors and how their characteristics may influence the particularities of the donation process. The present study aims to assess characteristics of donors and their newborns to identify associations with the amount of DHM and initiation and donation time, during the first and second year of the milk bank operation in Córdoba, Spain. Methods This cross-sectional study was conducted in three periods: pre-opening of the milk bank (PRE) including all women who gave birth to a newborn between January - May 2017 and were hospital users; donors in the first year after the opening (Period 1 (P1): April 2019 - March 2020); and in the second year (P2: April 2020 - March 2021). For P1 and P2, DHM data were recorded. The relationships between donor and newborn characteristics and the donation process were examined using univariable and regression models. Results From 391 women interviewed in the PRE period, 55 (14%) showed intention to donate. In P1 and P2, there were 51 and 25 human milk (HM) donors, respectively. Age, gestational age (GA) and parity were similar between periods. In P2, a higher proportion of donors had higher education (P1: 46%; P2: 70.8%, p = 0.045). Around 40% of donors in both periods were on maternity leave. In P1, donors who had low birth weight infants (< 2500 g) donated more HM than those with infants weighing ≥ 2500 g (p = 0.020). In P2, women whose GA was < 37 weeks donated a higher volume vs. those with ≥ 37 weeks (p = 0.002). Maternity leave was linked to a shorter initiation time for donations in both periods (P1: p = 0.002; P2: p < 0.001). Conclusions Data obtained from a Spanish human milk bank indicate that prematurity and low birth weight appear to influence the amounts of DHM. Employment status might be a decisive factor in initiating HM donation. Additional efforts are required to identify shared donor characteristics that influence the initiation and volume of donation.